2019
DOI: 10.1108/jpmh-07-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-term stressors and mental health distress following the 2013 Moore tornado: a pilot study

Abstract: Purpose Stress has considerable impacts on human health, potentially leading to issues such as fatigue, anxiety and depression. Resource loss, a common outcome of disasters, has been found to contribute to stress among disaster survivors. Prior research focuses heavily on clinical mental health impacts of disaster experience, with less research on the effect of cumulative stress during long-term recovery. To address this gap, the purpose of this paper is to examine the influence of stressors including resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“… Post-traumatic stress disorder (PTSD): We found in multiple studies that residents exposed to tornadoes reported PTSD or PTSD-related symptoms. Degree of tornado exposure, gender, age, emotional support, and barriers to a tornado warning were factors related to post-tornado PTSD [ 4 , 15 , 17 , 19 , 21 , 25 , 26 , 32 , 35 , 38 , 39 ]. PTSD, or symptoms associated with PTSD, was also found to be related to other mental and behavioral health needs such as depression [ 20 , 21 , 25 ], binge drinking [ 16 ], or substance abuse [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Post-traumatic stress disorder (PTSD): We found in multiple studies that residents exposed to tornadoes reported PTSD or PTSD-related symptoms. Degree of tornado exposure, gender, age, emotional support, and barriers to a tornado warning were factors related to post-tornado PTSD [ 4 , 15 , 17 , 19 , 21 , 25 , 26 , 32 , 35 , 38 , 39 ]. PTSD, or symptoms associated with PTSD, was also found to be related to other mental and behavioral health needs such as depression [ 20 , 21 , 25 ], binge drinking [ 16 ], or substance abuse [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Black and Latinx residents who reported difficulties receiving tornado warning alerts experienced more tornado exposure and adverse mental health impacts, and the intersections of ethnicity, language difficulties, citizenship, pre-mental health symptoms, and social class were also found to contribute to additional stressors [ 4 ]. Economic factors: Having lower income, renting, having debt, not having insurance, and loss of material resources were the significant risk factors for post-tornado adverse mental health symptoms [ 19 , 24 , 25 , 29 , 39 ]. However, there was one contradictory finding that, during long-term recovery from the Oklahoma Moore Tornado in 2013, loss of personal characteristics such as self-esteem or confidence were all statistically significantly associated with adverse mental health, whereas material loss did not correlate with mental health outcomes [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large scale disasters could have huge impact on affected populations through significant mental health tolls and behavioral changes ( Beaglehole et al, 2018 ; Clay and Greer, 2019 ; Parks et al, 2018 ). The COVID-19 pandemic drastically changed the world populations’ daily routines under a variety of infection control measures, such as lockdown, quarantine, and social distancing, while high prevalence of mental health problems was consistently reported ( Vindegaard and Benros, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic events trigger an on-set of exposure-related disturbance in daily activities ( Clay and Greer, 2019 ; Miller and Rasmussen, 2010 ). Negative changes in basic livelihood after traumatic events, such as chronic displacement among refugees predicted higher odds of subsequent mental health problems over and beyond the effects of trauma exposure ( Silove et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%